1986
DOI: 10.1104/pp.81.2.516
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies to Plant Growth Regulators

Abstract: ABSTRACIFour high affinity monoclonal antibodies, which recognize two plant growth regulators from the cytokinin group, namely trans-zeatin riboside and dihydrozeatin riboside and their derivatives are reported. Six hybridomas were produced from three independent fusions of Balb/c spleen cells with P3-NS1-Ag 4-1 (abbreviated NS1) or X63-Ag 8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…In contrast, the distribution of free cytokinin has not been resolved at the tissue level in the differentiation zone of roots. This might be due to the limited sensitivity of cytokinin antibodies (Eberle et al, 1986) and marker lines (Aloni et al, 2004) that cannot distinguish between different cytokinin types, precursors, and conjugated forms. Only recently has it been demonstrated that c-Z is the major active cytokinin isomer in maize roots (Veach et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the distribution of free cytokinin has not been resolved at the tissue level in the differentiation zone of roots. This might be due to the limited sensitivity of cytokinin antibodies (Eberle et al, 1986) and marker lines (Aloni et al, 2004) that cannot distinguish between different cytokinin types, precursors, and conjugated forms. Only recently has it been demonstrated that c-Z is the major active cytokinin isomer in maize roots (Veach et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…GFP under the control of the synthetic promoter Direct Repeat5 (DR5; Friml, 2003) is used to measure free indole acetic acid (IAA) auxin levels, while GUS under the control of the cytokinin-sensitive promoter ARR5 (Aloni et al, 2004) or TCS (Mueller and Sheen, 2008) is used to visualize free bioactive cytokinin levels. Alternatively, antibodies that recognize trans-zeatin riboside and dihydrozeatin riboside and their derivatives can be employed to measure cytokinin levels (Eberle et al, 1986). Direct measurements of hormones are particularly helpful to discriminate between hormone precursors and conjugates that cannot be detected via marker lines or antibodies.…”
mentioning
confidence: 99%
“…The following plant growth retardants were used: 1 -(4-trifluoromethyl)-2-( 1 ,2,4-triazolyl-( 1 ))-3-(5-methyl-1,3-dioxan-5-yl)-propen-3-ol (LAB 150 978 [14]), 5-(4-chlorophenyl)-3,4,5,9, 1 0-pentaaza-tetra-cyclo-5,4, 1,02,6,08,1"-dodeca-3,9-diene (tetcyclacis [ 13]). The structural formulas of the compounds used are shown in Figure 1 was extracted and the quantitative determination of phytohormones was performed by radioimmunoassay with a polyclonal antiserum for gibberellins according to (1) and by enzymeimmunoassay with mAB for 2-cis(+)ABA (17), cytokinins of the IPA-, ZR-, and DZR-types (5,30) and IAA (18). The antibodies were kindly provided by Professor E. W. Weiler (University of Osnabruck, FRG).…”
mentioning
confidence: 99%
“…For GA5 analysis an antiserum against GA, was used which crossreacts with the methyl esters of GA, (100%), GA3, (70%), GA4 (40%), GA5 (29%), GA7 (70%), GA8 (11%), GA9 (15%), and GA20 (55%) (1). For analysis of cytokinins of the ZR-type mAB of J3-I-B3 were used with cross reactivities especially against ZR (100%), zeatin riboside-5'-monophosphate (95%), and transzeatin (47%), and ofthe DZR-type mAB ofJ23-II-B1 with crossreactivities against DZR (100%) and dihydrozeatin (67%) were applied according to (5). For cross-reactivities ofthe mAB against IPA-type cytokinins, IAA and ABA see (17,18,30 [1,5,17,18,30).…”
mentioning
confidence: 99%
“…Polyclonal and monoclonal antibodies have been developed and used for quantification of a variety of plant growth regulators (3,4,11,13,16). With few exceptions (14), quantification by radioimmunoassay or ELISA is preceded by isolation and partial purification of the hormones from biochemically complex plant extracts (1,5,13).…”
mentioning
confidence: 99%